Diagnosis and Treatment of Neurocysticercosis - Christina M. Coyle; Herbert B. Tanowitz (Interdisciplinary Perspectives on Infectious Diseases)
Neurocysticercosis, the infection caused by the larval form of the tapeworm Taenia solium, is the most common parasitic disease of the central nervous system and the most common cause of acquired epilepsy worldwide. This has primarily been a disease that remains endemic in low-socioeconomic countries, but because of increased migration neurocysticercosis is being diagnosed more frequently in high-income countries. During the past three decades improved diagnostics, imaging, and treatment have led to more accurate diagnosis and improved prognosis for patients. This article reviews the current literature on neurocysticercosis, including newer diagnostics and treatment developments.